Identifying the Dimensions and Components of Good Governance and Organizational Development at Mazandaran University of Medical Sciences - Rezazadeh Taloukolaei, Fatemeh; Zameni, Farshideh; Enayati, Taraneh (Iranian Journal of Educational Sociology, 2022)
Purpose: Good governance and organizational development can create a competitive advantage for any organization, including educational institutions. Consequently, the purpose of this study was to identify the dimensions and components of good governance and organizational development at Mazandaran University of Medical Sciences.Methodology: This study was applied in purpose and qualitative in approach. The study population consisted of experts familiar with the research field at Mazandaran University of Medical Sciences. The research sample included 10 managers and professors at Mazandaran University of Medical Sciences, selected through purposive sampling based on the principle of theoretical saturation. Data were collected using semi-structured interviews, the validity of which was confirmed based on confirmability, credibility, and transferability, and reliability was calculated using a Holsti coefficient of 0.76. Data analysis was conducted using thematic analysis in MAXQDA-2020 software.Findings: The analysis results showed that good governance comprises 20 components across five dimensions: desirable governance, value orientation, capacity building, transparency, and accountability; and organizational development consists of 19 components across three dimensions: non-financial performance, financial performance, and organizational growth. Ultimately, a model of the dimensions and components of good governance and organizational development at Mazandaran University of Medical Sciences was developed.Conclusion: Utilizing the model designed in this study can assist professionals and officials at Mazandaran University of Medical Sciences in improving conditions and creating a competitive advantage.